Pengaruh variasi unsur Gd pada struktur kristal superkoduktor Y-358 (Y3-XGdxBa5Cu8O18- δ) - Suryana Deva Simanungkalit (Universitas Jenderal Soedirman, 2019)
Abstract - Research on the effect of Gd element variations on the Y-358 (Y3-xGdxBa5Cu8O18-δ). Superconducting crystal structure has been carried out. In this study the samples were held in a magnetic stirrer for 24 hours, calcined using a temperature of 600 ° C for 3 hours and sintering using a temperature of 900 ° C for 10 hours. The results of XRD characterization showed sharp peaks that indicate the occurrence of crystallization well. And each sample has the same functional group at a certain wave number. The functional groups found in each sample were Mono Aromatic, Para Aromatic, Ether Alcohol Anhydride, Esters, Nitro Carboxylic Acid (N = O), Alkyl CH (Stretching), Phenol Alcohol, OH Carboxyl Acid (alcohol, phenol, hydrogen bonds).